The impact of FDI on firm survival in Italy - Anna Ferragina; Rosanna Pittiglio; Filippo Reganati (FIW - Research Centre International Economics, 2009)
The aim of the analysis is to investigate the impact of inward FDI on Italian manufacturing and services firm survival. The paper is organized in two steps. First, we carry out theoretically and empirically the analysis of firm survival distinguishing between foreign multinationals, domestic multinationals and domestic non multinational firms. The empirical analysis is based on survival functions as well as a Cox proportional hazard model, controlling for firm and industry specific covariates. Second, we examine the effect of foreign presence on the survival of host country firms distinguishing between the impact on Italian-owned (indigenous) multinational and non multinational firms and on other foreign-owned firms (i.e., other MNEs) located in the host country. The finding reveals that during the period 2005-2007 while manufacturing and service firms owned by foreign MNEs are more likely to exit the market than national firms, on the other hand domestic MNEs have a higher chance of survival. These results stand even when other firm and industry specific variables are controlled for. This result support the idea that foreign MNEs are inherently footloose while Italian MNEs are more firmly rooted in the local economy. The estimates also indicate that older, larger and more productive firms have higher survival rates. Finally, firm survival of foreign MNEs and domestic MNEs is unaffected by the increased presence of foreign MNEs. On the other hand, the increased foreign presence has a positive impact on Italian non-MNEs' survival only in the service sector.
Keywords: L25; F23; C41; F23; J31; 330; Domestic firms; Multinational Enterprises; Survival Analysis